Challenges of urban integration in Chile: Residential segregation and the role of advanced human capital under neoliberal influences - Correa Parra, Juan Pablo.; Vergara Perucich, José Francisco.; Rodríguez Valladares, Norma.; Aguirre Núñez, Carlos.; Hidalgo Dattwyler, Rodrigo. (Universidad de Chile, 2023)
This study explores residential segregation in Chile, focusing on advanced human capital as an indicator of socioeconomic status. Using data from the 2002 and 2017 census, segregation at national, regional, and communal scales is addressed using the dissimilarity index. The findings reveal marked segregation in the main cities. Speculatively, segregation levels are so high that it would be necessary to relocate 54% of the population to significantly increase levels of urban integration. From more evidence-based approaches, these findings imply the importance of decentralizing education and creating housing conditions that promote productivity and innovation. The research concludes that neoliberal policies have limited the construction of integrated cities, and that existing strategies have been insufficient to address the root causes of inequality and residential segregation in Chile.
Desafíos de integración urbana en Chile: Segregación residencial y el rol del capital humano avanzado bajo influencias neoliberales
Keywords: Advanced human capital; Dissimilarity; Políticas públicas; Segregación residencial